Evaluation of pure and Ag-doped TiO2 films in the photocatalytic activity of phenol - Araujo, Adriana Barbosa [UNESP]; Jorge, Sônia Maria Alves [UNESP]; Padilha, Pedro de Magalhães [UNESP]; Bozano, Dorotéia de Fátima [UNESP]; Castro, Gustavo Rocha de [UNESP]; Florentino, Ariovaldo de Oliveira [UNESP] (My University, 2015)
Pure TiO2 films, modified by the addition of Degussa P25 powder and Ag-doped were synthesized using sol-gel route and immobilized in borosilicate support at different withdrawing rates and dipping time. They were characterized by X-ray diffractometry, scanning electronic microscopy and high-resolution field-emission gun scanning electronic microscopy. Their photocatalytic activities under UV irradiation were examined using phenol. The higher activities were achieved through the Ag-doped films deposited with 0.4 mm s-1 and two dipping. Approximately 90% of the organic contaminant was photodegradated after 24 h of irradiation.
Keywords: TiO2 films; Photocatalysis; Doping; Phenol; Photodegradation